PSIX-28 Parity and lactation stage affect the sow milk microbiome. (8th October 2021) - Henniger, Madison T; Rempel, Lea A; Oliver, William T; Miles, Jeremy R; Lindholm-Perry, Amanda; Myer, Phillip R
Abstract: The milk microbiome in swine has been recently demonstrated to develop and alter the growing gut microbiome in offspring. Milk is the primary nutritional source for piglets and the established microbial communities from initial diet remain stable over time, thus being critical for long-term effects on the animal. Since little is known about the ontogeny of the milk microbiome, the objective of this study was to determine differences in the sow milk microbiome among multiple parities and days in lactation. A total of 32 sows were grouped by parity, 1–4, with 8 sows per parity. Sows were on the same diet and had ad libitum access to water. At sampling, teats were cleaned and stripped. Milk samples were manually collected on one side from a fore, mid, and hind teat, then combined for one whole milk sample per animal. Milk was sampled on days 2 and 16 to determine differences between days in lactation. Samples were sequenced using an Illumina MiSeq for V1-V3 regions of the bacterial 16S rRNA gene and downstream analyses were conducted in the R environment using 'phyloseq' and 'DADA2' packages. Statistical analyzes utilized a completely randomized design and a mixed model analysis of variance, with fixed effects of parity and days in lactation and examining a parity by day interaction. The genera Corynebacterium were greater (P < 0.05) abundance in parity 4. There was an increase (P < 0.05) in Staphylococcus at day 2 compared to day 16. Core microbial communities, Lactobacillus and Romboutsia increased (P < 0.05) by day 16. Identifying microbial communities present in the milk microbiome in sows can allow producers to understand how these microbes may influence the gut microbiome in growing piglets to augment gain. USDA is an equal opportunity provider and employer.